2022
DOI: 10.1002/rnc.5965
|View full text |Cite
|
Sign up to set email alerts
|

Dwell‐time‐based control synthesis of switched positive systems with all unstabilizable subsystems

Abstract: This article investigates the robust exponential stabilization of a class of switched positive systems with uncertainties by co-designing controllers for subsystems and dwell time switching strategy. The uncertainties refer to interval uncertainties. One of the distinguishing features is that none of the forced individual subsystems is assumed to be stabilized. The other feature is that the stabilization for the unforced switched system can not be solvable by designing dwell time switching signal. First, for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Next, Zhang and Sun [26] examined the practical exponential stability (ES) of discrete-time linear SPSs with impulse and AUMs. Moreover, An et al [28] investigated the robust exponential stabilization of SPSs with uncertainties based on the assumption that none of the individual modes is stabilizable. From the results in [20,26,28], it should be observed that the existence of the TVD was not taken into account in the systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Zhang and Sun [26] examined the practical exponential stability (ES) of discrete-time linear SPSs with impulse and AUMs. Moreover, An et al [28] investigated the robust exponential stabilization of SPSs with uncertainties based on the assumption that none of the individual modes is stabilizable. From the results in [20,26,28], it should be observed that the existence of the TVD was not taken into account in the systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, An et al [28] investigated the robust exponential stabilization of SPSs with uncertainties based on the assumption that none of the individual modes is stabilizable. From the results in [20,26,28], it should be observed that the existence of the TVD was not taken into account in the systems. Furthermore, there are beneficial results about switched positive time-varying delay systems (SPTVDSs) in cases in which all modes are unstable, reported briefly in the following.…”
Section: Introductionmentioning
confidence: 99%
“…Switched positive systems are typically featured by switched systems with the positivity constraint on the state (and possibly input or output) variables. [1][2][3][4][5][6][7] In recent years, considerable attention has been attracted to the related exploration owing to the positive nature and their practical applications in numerous engineering practice, such as communication networks, 8 formation flying, 9 and compartmental systems. 10 This article, based on the non-negative state space, centers on devising the state-driven switching mechanism for switched positive time-delay systems, and simultaneously characterizes the mechanism by constructing the step-dependent multiple linear copositive Lyapunov-Krasovskii functionals (CLKF).…”
Section: Introductionmentioning
confidence: 99%
“…Switched positive systems are typically featured by switched systems with the positivity constraint on the state (and possibly input or output) variables 1‐7 . In recent years, considerable attention has been attracted to the related exploration owing to the positive nature and their practical applications in numerous engineering practice, such as communication networks, 8 formation flying, 9 and compartmental systems 10 .…”
Section: Introductionmentioning
confidence: 99%